Re‐designing infrastructure as a strategy for crafting coherence across three networks focused on the implementation of the next generation science standards. Issue 7 (24th March 2021) - Hall, Jonathan L.; Campbell, Todd; Lundgren, Lisa
Abstract: This design‐based research project reports on three multilevel networks that were focused on implementing the Next Generation Science Standards (NGSS). Given the recent attention to understanding infrastructure to craft coherence in NGSS implementation, this research investigated how these networks iteratively re‐designed infrastructure as they engaged in implementing the NGSS. This focus is particularly important in the current context of NGSS implementation since needed infrastructure did not accompany the dissemination of the standards. The three networks were the following: mentor teachers, district specialists, and interim assessment specialists. Qualitative cases based on recordings of network working sessions, interviews with members, and artifacts of their work were generated for each network and then compared and contrasted. Findings show the work on infrastructure re‐design across the networks not only involved identifying useful NGSS‐designed resources and frameworks, but also translating these into meaningful supports or scaffolds that could ultimately lead to productive forms of engagement for either supporting teacher professional learning or student learning. Also, collegial workspaces were beneficial for institutionalizing networks' foci by creating spaces for all actors to share their experiences, challenges, and needs. This meant focusing on curriculum and instructional routines for mentor teachers, focusing on NGSS instructional principles for district leaders, and focusing on the development of an interim assessment practice brief for interim assessment leaders—foci identified as central to and immediately applicable in the day‐to‐day work of the respective network members.